2017
DOI: 10.1186/s12985-017-0687-7
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and pathogenesis of aerosolized eastern equine encephalitis in the common marmoset (Callithrix jacchus)

Abstract: BackgroundLicensed antiviral therapeutics and vaccines to protect against eastern equine encephalitis virus (EEEV) in humans currently do not exist. Animal models that faithfully recapitulate the clinical characteristics of human EEEV encephalitic disease, including fever, drowsiness, anorexia, and neurological signs such as seizures, are needed to satisfy requirements of the Food and Drug Administration (FDA) for clinical product licensing under the Animal Rule.MethodsIn an effort to meet this requirement, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Virus distribution and load was comparable with Honnold et al I, [7] in the brain, although unsurprisingly a generally higher viral load was observed in the lung, spleen and blood of mice exposed to 100 × LD 50 EEEV FL93–939 than described here. Exposure of marmosets to EEEV by the aerosol route culminates in a very similar disease course, where clinical signs were observed from 3 to 4 days post challenge, and included ruffled fur, lack of grooming and progressively, loss of balance, subdued behaviours, tremors and death in animals exposed to high doses of the virus (> 1 × 10 3 pfu inhaled dose) [12]. Unlike rodent models, the higher the challenge dose of virus the lower the MTTD and the earlier severe clinical signs were observed in marmosets, with a dose-dependent MTTD range of 4–19 days for animals that succumbed to disease.…”
Section: Discussionmentioning
confidence: 99%
“…Virus distribution and load was comparable with Honnold et al I, [7] in the brain, although unsurprisingly a generally higher viral load was observed in the lung, spleen and blood of mice exposed to 100 × LD 50 EEEV FL93–939 than described here. Exposure of marmosets to EEEV by the aerosol route culminates in a very similar disease course, where clinical signs were observed from 3 to 4 days post challenge, and included ruffled fur, lack of grooming and progressively, loss of balance, subdued behaviours, tremors and death in animals exposed to high doses of the virus (> 1 × 10 3 pfu inhaled dose) [12]. Unlike rodent models, the higher the challenge dose of virus the lower the MTTD and the earlier severe clinical signs were observed in marmosets, with a dose-dependent MTTD range of 4–19 days for animals that succumbed to disease.…”
Section: Discussionmentioning
confidence: 99%
“…In these previous studies, virus was localized almost exclusively in the brain and was readily detected in the frontal cortex, corpus striatum, thalamus, hippocampus, mesencephalon, pons, medulla oblongata, and cerebellum [11][12][13][14]. In contrast, EEEV could not be detected in the heart, liver, lung, spleen, and kidney of guinea pigs and marmosets [11,14].…”
Section: Discussionmentioning
confidence: 86%
“…The dissemination of EEEV following aerosol infection has not been investigated in previous macaque studies; however, it has been examined in mice, guinea pigs, and marmosets [11][12][13][14]. In these previous studies, virus was localized almost exclusively in the brain and was readily detected in the frontal cortex, corpus striatum, thalamus, hippocampus, mesencephalon, pons, medulla oblongata, and cerebellum [11][12][13][14]. In contrast, EEEV could not be detected in the heart, liver, lung, spleen, and kidney of guinea pigs and marmosets [11,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon publication of the original article [ 1 ], it was noticed that the author's correction requests for Table 2 had not been incorporated, due to an error in the systems. These corrections are listed below and have also been corrected in the original article:…”
Section: Erratummentioning
confidence: 99%